Using ICT in teaching and learning English at MAN 1 Kota Gorontalo - Abdulrahman, Fajriani; Akhmad, Zulkifli; Amalina, Nur (Journal of English Teaching and Linguistic Issues (JETLI), 2022)
This research aims to identify the types of ICT equipment and to describe the use of ICT in English Language Teaching and Learning by English teachers at MAN I Kota Gorontalo. The research employs a descriptive qualitative method with interviews and documentation from lesson plan in the data collection. Ten students of class X and XI in the second semester of 2019/2020 and two English teachers were involved in this research. The data were analyzed by reducing data, displaying, and then drawing the conclusions. The result showed that the first was the type of media used by the teachers in teaching and learning process are: laptops computers, LCDs, Sound systems, Power Points, Google Classroom Google Forms, and WhatsApp groups. Second, the teaching and learning process of ICT-based media has been included in Lesson Plan (RPP) by supporting applications such as PowerPoints for presenting initial material creating WhatsApp groups for assignment submissions, and Google class Google forms for evaluation. Apan from the use of ICT-based media, other learning resources are in form of English books There is also collaboration between media and methods in learning Suggestion are given to schools, teachers and further researchers.